(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study investigated the product packaging as predictor of brand loyalty and habitual buying behaviour of Business Education undergraduate in public universities in Anambra State. The study was guided by two hypotheses. This study adopted a correlational survey research design and used multi-stage sampling technique – proportionate stratified and convenience sampling technique. The population comprised 535 business education regular students in public universities in Anambra State. The sample size of the study was 119 business education students. A structured questionnaire was used as the instrument for data collection. The questionnaire was validated by experts in Business Education and subjected to reliability test using Cronbach Alpha resulting to coefficient value of .841, .793 and .813 respectively for the three clusters of the questionnaire. Google form was used to simplify data collection. The data were examined using regression analysis and Pearson Product Moment correlation. The study found that product packaging does not significantly predict brand loyalty as it predicts business education student’s habitual buying behavior in public universities in Anambra State. Based on the findings of the study, it was recommended that brands should create packaging that clearly communicate the value of product on the packaging for easy identification of the unique features, benefits or cost savings among others.